Carmenta chromolaenae Eichlin, a new species (Lepidoptera: Sesiidae) for the biological control of Chromolaena odorata (L.) King & Robinson (Asteraceae) - Eichlin, Thomas D.; Delgado, Oona S.; Strathie, Lorraine W.; Zachariades, Costas; Clavijo, Jose (Zootaxa, 2009)
A new species of Sesiidae, Carmenta chromolaenae Eichlin, is described to make the name available to researchers evaluating the moth’s potential for biological control of its host plant, Chromolaena odorata, in South Africa and other parts of the plant’s invasive range. This clearwing moth species was reared from the host plant in Venezuela. The adult moth, including the male and female genitalia, larva, and pupa are described and illustrated. Its biology and possible use as a control agent are discussed.